The Role of Social Worker in the Context of Refugees and Asylum Seekers Rights in Indonesia - Alamsyah Agus; Intan Slipi Lia; Muhammad Akbar (Asian Social Work Journal, 2018)
The plight of refugees and asylum seekers has been a trending issue of critical importance for social workers in Indonesia. At the end of February 2018, the public was overwhelmed by mass media coverage of the large number of refugees living on the streets in front of the Immigration Office in Jakarta. Their existence needs to be noticed by the government in particular and all parties in general. In fact, many of the difficulties experienced by refugees and asylum seekers in Indonesia, but the most felt is due to the issue of legal status and limitations in the language of communication, they can not access public services such as health care, education, work, and others. The plight of them must necessarily be a very important concern for social workers in Indonesia, as it may create new social problem. Social workers work to uphold the dignity of all those refugees and asylum seekers including unaccompanied minors (UAM) and to work with them for successful social functioning. This paper explores available integrative literature, quantitative document analysis, and presents mixed methodology through individual interviews and an exploratory study to analyze social workers’ role to respond the various issues faced by today’s refugees and asylum seekers rights as well as potential way for being supporting document as a policy framework for Indonesian government to ratify the 1951 Refugee Convention.